Naqd and Islah : Ibn ‛Ashur’s comprehensive critique and reform efforts regarding Islamic learning and education - El-Mesawi, Mohamed El-Tahir (ISTAC, 2012)

(untitled)
This article examines the theoretical and practical work of the Tunisian scholar and outstanding Imam of the ZaytËna Grand Mosque Muhmmad al-Tāhir Ibn ‛ashur con-cerning the reform of Muslim education. It analyzes his systematic and all-encompassing criticism of the body of Islamic learning and its institutional frame-work at the late nineteenth and early twentieth centuries. Special attention has been given to highlighting Ibn ‛ÓshËr’s identification of the internal and external factors that led to the decline of Muslim education and left it in a state of crisis, unable to cope with the modern challenges of life. The article also brings into light Ibn ‛Ashur’s theoretical and practical approach rejuvenating Islamic education in accordance with its original spirit and worldview. Meanwhile, the author indirectly brought home the pioneering character and relevance of Ibn ‛Ashur’s views to the ongoing discourse on Islamization of knowledge. Key terms: education and learning, Islamic education, reform, Islamization of knowledge, criticism.